METHODICAL ASPECTS OF PEDAGOGICAL TECHNOLOGY OF TEACHING OF SCHOOLBOYS IN THE PROCESS OF STUDY OF ARTISTIC GRAPHIC ARTS - Serdotetska, Ya.M. (Pedagogy of Higher and Secondary Education, 2022)
In the article is regarded the questions of the methodic pedagogical technology of learning students the based of art graphic.